The Ethical Issues of Aviation Business in Indonesia - Dinar Dewi Kania (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
Aviation business in Indonesia still has a bad image in the international community because of some ethical cases involving the airline companies. The purpose of this study is to explore the ethical issues of aviation business in Indonesia and to find out how to improve the application of business ethics. This research is an explorative study. Data is obtained through observation, literature study and in-depth interviews with key-informants regarding the ethical issues of aviation business in Indonesia. The results show that the critical issues in aviation business ethics in Indonesia has been identified: 1) the issue of flight safety, 2) environmental issues, and 3) the issue of professional ethics, specifically drug abuse by pilots and crew. The efforts that should be made to improve the application of business ethics in aviation services are to build a corporate culture that has philanthropic responsibility and to make public policy based on moral values, religion and Indonesian culture.